Business Investment Feasibility Study Coffeeshop Portable - Venus Khatta Salsabillah (Universitas Pancasakti Tegal, 2024)
Drinking coffee has become a lifestyle trend nowadays, characterized by growth of coffee-based café industry increased by 16%-18%. But since the Covid-19 pandemic hit Indonesia, it has had a variety of economic impacts including the existence of coffee shops. The idea of portable coffee shop business became a new breakthrough for businesses in facing this pandemic era. The purpose of this research is to know this feasiblity of this business if reviewed in terms of financial aspects. This study used the least square method to predict its demand. Through the processing and discussion of data that has been done, resulting in NPV of Rp. 45,658,665 > Initial investment, IRR of 36.8% greater than the interest of banks in general, PP with a capital return time of 10 months 6 days. and PI of 3.43 > 1. From these criteria Coffeshop Portable is declared eligible.